Implementasi Kitab Akhlak Lil Banin dalam Membentuk Akhlak Siswa di SMP IT Nurul Ihsan Purwakarta - Nurjanah, Siti; Wulandari, Dyah; Hamid, Tb. Abdul (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2022)
This research is motivated by the development of the times which greatly affect the morals, behavior, ethics and morals of the student party caused by the ease of accessing the internet so that phenomena, news, and events can be obtained easily. In this case, schools play an important role in balancing the development of the times through moral education. This research is based on Roykan's theory which states that the book of Akhlak lil banin is suitable to be implemented with the development of adolescent children. This study uses a qualitative approach with a field research methodology. Data collection techniques used are in-depth interviews, observation, and documentary studies. The analysis technique uses data reduction, data presentation, and conclusions. While testing the validity of the data using the source triangulation technique and the triangulation technique. The results of the study show that: 1) Teachers of the book of Akhlak lil banin have met the qualifications of teacher competence even though they are not yet fully optimal. 2) The essence of the book Akhlak lil banin volume one contains the morals that a child must have, volume two contains the obligations of a child and volume three contains the etiquette that a child must do. 3) The book of lil banin morality is very influential and acts as a behavioral controller gradually from class VII to class IX.